National policy in education in great britain and the united states - Balatska, Natalia I.; Pysmenna, Olga O. (Proceedings of National Aviation University (archive), 2009)
The article deals with some pressing issues faced by high and highest schools in Great Britain and the USA. Considered are educational, organisational, financial, psychological problems and their social effects in the framework of general characteristics of new trends in education. Analysed are the latest publications in the press and some statistics are given.